Urban expansion in the south of Ilhéus-BA: horizontal closed condominiums and segregation - Lanza, Fabiana Portilho de Resende; Batata, Adriane Gomes Rodrigues (Technical and Scientific Journal Green Cities, 2022)
Urban expansion processes in both medium-sized and large cities have been influenced by a new form of urban space production, closed condominiums. Increasingly present in the city landscape, this typology reflects the desire of specific social groups that, stimulated by the real estate market, impact the urban and social fabric by establishing different forms of segregation. The work seeks to contribute to the discussion regarding the impact of the proliferation and consolidation of horizontal closed condominiums in medium-sized cities, such as the municipality of Ilhéus, BA. The main results found suggest a certain inefficiency of the municipal public administration in enforcing urban legislation, associated with strong pressure from the real estate market to negotiate the landscape. This context results in different processes of segregation, such as that associated with urban mobility. KEYWORDS: Medium cities. Space production. Segregation. Social agentes. Landscape.